SAT0222 CLINICAL SPECTRUM AND LONG TERM FOLLOWUP OF SYSTEMIC LUPUS ERYTHEMATOSUS-ASSOCIATED MACROPHAGE ACTIVATION SYNDROME. (13th June 2020) - Okano, T.; Saegusa, J.; Yoneda, K.; Shirasugi, I.; Ueda, Y.; Akashi, K.; Onishi, A.; Morinobu, A.
Abstract : Background: Systemic lupus erythematosus (SLE) patients present with variable clinical features ranging from mild joint and skin involvement to life-threatening organ involvement such as nephritis, neuropsychiatric involvement, diffuse alveolar hemorrhage, and hemophagocytic lymphohistiocytosis (HLH). HLH is rare, but fatal complication of SLE. Recently, European League Against Rheumatism, the American College of Rheumatology, and the Pediatric Rheumatology International Trials Organization was to develop a set of classification criteria for MAS complicating systemic juvenile idiopathic arthritis (PRINTO criteria) [1]. Sung Soo Ahn and his colleagues reported PRINTO criteria predicted mortality of adult SLE patient, but they followed only one year [2]. Objectives: To reveal association PRINTO criteria with long term mortalities in SLE patient in our Hospital. Methods: We performed a retrospective analysis of SLE patients who received moderate dose glucocorticoid therapy (>0.4mg/kg/d) in our hospital between April 2008 and April 2019. Patients were evaluated for HLH using the 2016 PRINTO classification criteria for MAS. Clinical features and laboratory findings were compared and overall survival rate was analyzed. Results: Among 164 episode (144 patients) with SLE, 31 episode (31 patients) 5.2% were considered to have MAS on admission. The overall survival rate was significantly lower in patients with MAS than without MAS (86.2% vs. 95.3%, p = 0.048). Interestingly, SLEDAI had no association with mortality, relapse rate, and MAS complication. SLEDAI more focused on renal and neuropsychiatric symptoms than hematologic features. So SLEDAI might not be associated with MAS secondary to SLE. Furthermore, we observed no death patient with MAS after one year, and only 1 case relapse in MAS patient. So MAS might have fatal but less relapsing property compared with other lupus cases. Conclusion: PRINTO criteria may be useful to differentiated fatal MAS patients from others. Further investigations are required to confirm our findings. Limitation The main limitations of our study include its retrospective design, single center site, and that the number of admitted patients with SLE was small. Limitation: The main limitations of our study include its retrospective design, single center site, and that the number of admitted patients with SLE was small. Limitation: Limitation The main limitations of our study include its retrospective design, single center site, and that the number of admitted patients with SLE was small. References: [1]Wulffraat N, Schneider R, Filipovic L, et al. 2016 Classification Criteria for Macrophage Activation Syndrome Complicating Systemic Juvenile Idiopathic Arthritis. Ann Rheum Dis 2016;75:481–9. [2]Ahn SS, Yoo BW, Jung SM, et al. In-hospital mortality in febrile lupus patients based on 2016 EULAR/ACR/PRINTO classification criteria for macrophage activation syndrome. Semin Arthritis Rheum 2017;47:216–21. Disclosure of Interests: None declared